2015
DOI: 10.1002/jhet.2487
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis and Antibacterial Activity of Pyrido[2,3‐d]Pyrimidine, Chromeno[3,4‐c]Pyridine, Pyridine, Pyrimido[2,3‐c]Pyridazine, Enediamines, and Pyridazine Derivatives

Abstract: A series of Pyrido[2,3‐d]pyrimidine have been synthesized through a reaction of cyanoacetylurea derivatives with aromatic aldehydes or Arylidines. Reaction of compound 1 with aromatic arylidine derivatives or arylhydrazones gave Chromeno[3,4‐c]pyridine, Pyridine, Pyrimido[2,3‐c]pyridazine, Enediamines, and Pyridazine derivatives. All the synthesized compounds were confirmed by spectral studies and screened for their in antibacterial activity against Staphylococcus aureus (Gram positive) and Escherichia coli (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Antibacterial activity was performed for all the targeted compounds against E. coli and S. aureus strains using gentamicin as a standard drug. From the data of the antibacterial activity, it was observed that the compounds 316 , 320 , 319 , 322 and 321 had displayed tremendous activity across all the strains with a 16.5 to 24mm zone of inhibition (ZOI) value compared to the reference drug (ZOI 15 mm) [ 39 ]. Pyrimidine ( 326 – 332 ) and pyridine ( 333 – 341 ) were synthesized according to Scheme 26 and screened against different bacteria [ 40 ].…”
Section: Antibacterial Activity Of Heterocyclic Compoundsmentioning
confidence: 99%
“…Antibacterial activity was performed for all the targeted compounds against E. coli and S. aureus strains using gentamicin as a standard drug. From the data of the antibacterial activity, it was observed that the compounds 316 , 320 , 319 , 322 and 321 had displayed tremendous activity across all the strains with a 16.5 to 24mm zone of inhibition (ZOI) value compared to the reference drug (ZOI 15 mm) [ 39 ]. Pyrimidine ( 326 – 332 ) and pyridine ( 333 – 341 ) were synthesized according to Scheme 26 and screened against different bacteria [ 40 ].…”
Section: Antibacterial Activity Of Heterocyclic Compoundsmentioning
confidence: 99%
“…Among the heterocyclic compounds, pyridine and their analogues are the most interesting structural units due to their broad spectrum of applications [ 1 ] in natural products, [ 2 ] pharmaceutical, [ 3 ] agrochemical, [ 4 ] and material science. [ 5,6 ] Many of the fused pyridine compounds have been confirmed as valuable candidates possessing anti‐bacterial, [ 7 ] anti‐fungal, [ 8 ] anti‐microbial, [ 9 ] anti‐oxidant, [ 10,11 ] anti‐cancer, [ 12,13 ] anti‐psychotic, [ 14 ] anti‐inflammatory, [ 15,16 ] anti‐leishmanial, [ 17 ] anti‐viral, [ 18 ] antihypersensitive, [ 19 ] anti‐convulsants, [ 20 ] anti‐malarial, [ 21 ] potassium channel openers, [ 22 ] anti‐diabetic, [ 23 ] and anti‐tumor activities. [ 24 ] Spiro compounds having cyclic structures fused at a central carbon are of interest due to their interesting conformational features and their structural implications on biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Thienopyrimidines, including the three fundamental systems (thieno[2,3‐ d ]pyrimidine, thieno[3,2‐ d ]pyrimidine, and thieno[3,4‐ d ]pyrimidine), are among those fused pyrimidines that are found to have a wide variety of pharmacological activities. Many thienopyrimidines have been found to exhibit a variety of pronounced activities as antimicrobial , anticancer , and antiviral agents. Moreover, the literatures advertised that thienopyrimidines bearing furan moiety (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Fused pyrimidines have attracted considerable interest in the medicinal chemistry research because of their versatility and wide bioactive potential . Thienopyrimidines, including the three fundamental systems (thieno[2,3‐ d ]pyrimidine, thieno[3,2‐ d ]pyrimidine, and thieno[3,4‐ d ]pyrimidine), are among those fused pyrimidines that are found to have a wide variety of pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%